Examining the Conditions Affecting the Success of Income-generating Activities by Refugees: A focus on Programs provided by INGOs in Egypt. - Elkorashy, Wesal (AUC Knowledge Fountain, 2023)
With the global decline in resettlement opportunities for refugees in the so-called Global North, many displaced populations are hosted in the Global South. The shift towards first asylum and transit countries often places them in environments where economic stability is often elusive, coupled with legal, social, and cultural barriers. In this challenging situation, addressing refugees' economic lives resilience, and their contribution in the overall economy of host countries becomes increasingly urgent. This is intrinsically linked to the support provided by humanitarian organizations, particularly INGOs, which play a pivotal role in implementing economic programs aimed at increasing refugees’ engagement in the labor market and fostering self-reliance. In alignment with the analytical and dynamic global changes, the study aims to delve into the economic lives of refugees in Egypt by examining the conditions affecting the success of carrying out Income-Generating Activities (IGAs) by refugees, with a focus on economic programs provided by INGOs. By exploring the factors influencing such a success, including refugees’ human and social factors as well as the design and implementation of economic programs, the study addresses the contribution of these activities in enhancing the refugees’ self-reliance during their stay in Egypt. The findings of this thesis reveal the essential role INGOs play in enhancing refugees' capability to engage and succeed in IGAs, building upon their substantial human and social capital. The study suggests that the longer the refugee stays in countries of asylum, the greater probability of success in managing their IGAs and increasing self-reliance.